Detection of the recurrence of superficial urothelial carcinoma of urinary bladder by combined urine cytology and cystoscopy - Rahman, Mohammad Shafiqur; Siddique, A. S. M. Azizur Rahman; Islam, Mohammad Saiful; Habib, Saequa; Ahmed, Faika Farah (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The study was aimed to evaluate the accuracy of combined urine cytology and cystoscopy for the detection of the recurrence of superficial urothelial carcinoma of urinary bladder without bladder biopsy. A total 60 patients [males 48, females 12; age range 41-80 years (mean age- 63.15 years)] were included. Urine cytology as well as cystoscopy were done with a targeted biopsy taken from any apparently visible growth in the bladder. The systematic biopsy was taken where there was no growth. Reports of the cytology and cystoscopy were compared with the histopathology reports. It was found that 18 patients were cytology positive (false positive 2) and 42 patients were cytology negative (false negative 10) with sensitivity 61.5% and specificity 94%. During cystoscopy 24 patients were found recurrent growth in the bladder (false positive 3) and 36 patients were negative (false negative 5) with sensitivity 80.7% and specificity 91%. But when combined urine cytology and cystoscopic findings evaluated, the sensitivity and specificity were found 100% and 91% respectively. In conclusion, combined urine cytology and cystoscopy can be used for the detection of recurrence of superficial urothelial carcinoma of urinary bladder.